2017
DOI: 10.1159/000472146
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Gene Expression Profiling for Prostate Cancer Risk Assessment: A Systematic Review

Abstract: Objectives: The aim of the study is to review biotechnology advances in gene expression profiling on prostate cancer (PCa), focusing on experimental platform development and gene discovery, in relation to different study designs and outcomes in order to understand how they can be exploited to improve PCa diagnosis and clinical management. Methods: We conducted a systematic literature review on gene expression profiling studies through PubMed/MEDLINE and Web of Science between 2000 and 2016. Tissue biopsy and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 150 publications
0
8
0
1
Order By: Relevance
“…Past research 15,16 has addressed the effectiveness of genomic testing with little attempt to dissect behavioral predictors of testing uptake among ethnic subpopulations. While research on the issue is scant, this study’s findings mirror reported notions that hesitancy about genomic testing participation may stem from lack of knowledge rather than from the procedure itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research 15,16 has addressed the effectiveness of genomic testing with little attempt to dissect behavioral predictors of testing uptake among ethnic subpopulations. While research on the issue is scant, this study’s findings mirror reported notions that hesitancy about genomic testing participation may stem from lack of knowledge rather than from the procedure itself.…”
Section: Discussionmentioning
confidence: 99%
“…The current study’s findings expand on previous studies demonstrating lower consent rates for genetic-variation research among blacks compared with other ethnic groups 14 by examining minority-male perceptions of genomic testing. Past research 15,16 has addressed the effectiveness of genomic testing with little attempt to dissect behavioral predictors of testing uptake among ethnic subpopulations. While research on the issue is scant, this study’s findings mirror reported notions that hesitancy about genomic testing participation may stem from lack of knowledge rather than from the procedure itself.…”
Section: Discussionmentioning
confidence: 99%
“…Однако только в 3 исследованиях учитывалась степень злокачественности опухоли [20]. В 2 из них изучались сигнатуры с участием 29 и 41 гена [21][22][23]. Профили экспрессии были получены с мРНК, экстрагированной из немикродиссектированных тканей, что может привести к смещению из-за потенциального «загрязнения» прилегающей нормальной ткани, воспалительных клеток или эндотелиальных клеток, но генные классификаторы были клинически ассоциированы с опухолями низкой и высокой степени злокачественности [24,25].…”
Section: применение подхода In Silicounclassified
“…[6][7][8] However, only a few have been associated with cancer outcomes and often with inconsistent results. 9 Specifically, antitumor genes could reveal new insights into molecular mechanisms of PCa pathogenesis and be a promising approach for gene therapy of PCa. 10,11 However, compared to other cancers such as breast or colorectal cancers, 12,13 little has been described regarding antitumor genes in PCa.…”
Section: Introductionmentioning
confidence: 99%